The macroeconomic impact of extreme weather: Evidence from Jamaica. (July 2021) - Campbell, Alrick; Spencer, Nekeisha
Abstract: A common concern for many developing countries is effectively mitigating the economic impact of extreme weather. While these damages provide some foresight for planning, how they translate into a loss of economic output remains unclear. To add clarity to the literature and provide a basis for resilient policy making, we quantify the macroeconomic impact of extreme weather in Jamaica, one of the most environmentally vulnerable countries in the Caribbean. To achieve this, we build a quarterly dataset on weather and the most weather-susceptible productive sectors that help drive the macroeconomy. We utilise a vector autoregressive econometric model to extract the direct impact of weather and incorporate any feedback mechanisms. Our estimates reveal an immediate large negative impact of hurricanes with signs of economic recovery at least two quarters after a storm strike, a delayed negative impact of temperature which dissipates two years later and a favourable impact of rainfall. We derive implications for policy regarding sustainable productivity and recovery strategies.